Mycosis Fungoides mimic chronic eczema? Observation - Jacek Andruszkiewicz; Piotr Brzezinski (Our Dermatology Online, 2013)
Mycosis fungoides (MF) is the most common type of cutaneous T-cell lymphoma [1]. Because of its great variety of clinical features and nonspecific histological findings (especially in early stages) has been named the "great imitator "and can induce many wrong diagnosis [2,3]. Mycosis fungoides (MF), is an epidermotropic lymphoma included as an indolent form in the recent WHO/EORTC classification. From a clinical point of view, the classic disease progression usually is slow and takes over years or even decades, and characterized by the evolution from patches to more infiltrated plaques and eventually to tumours or erythroderma. However, the analysis of the MF disease course has been greatly impaired by the rarity of the disease, thus data about the time course of disease progression and pattern of relapse during time are not well known [4,5]. Therefore very often Mycosis fungoides is misdiagnosed as chronic eczema [6]. MF can also mimic: vitiligo [6], alopecia-Areata [7], ecchymosis [8].